Analysis Determinants of Capital Structure on Sharia Commercial Banks - Mayasari, ine; Humam, Muhammad (PT Larva Wijaya Penerbit, 2024)
This research aims to analyze the influence of profitability, liquidity and asset structure on the capital structure of Sharia Commercial Banks in Indonesia for the 2018-2022 period. The independent variables in this research consist of profitability using the Return on Assets (ROA) ratio, liquidity using the Financing to Deposit Ratio (FDR) ratio, and asset structure using the Fixed Asset Ratio (FAR) ratio, as well as the dependent variable in the form of capital structure using Debt to Equity Ratio (DER). The sampling technique used purposive sampling from a population of 15 Sharia Commercial Banks to 11 Sharia Commercial Banks. This research is quantitative research using secondary data. Secondary data was taken from financial reports or annual reports of Sharia Commercial Banks for the 2018-2022 period. The research method used is quantitative with a descriptive approach. Data analysis was carried out using the panel data regression method. The results of this research are that the profitability and liquidity variables have no influence on the capital structure of Sharia Commercial Banks for the 2018-2022 period, while the asset structure variables have an influence on the capital structure. The capital structure of Sharia Commercial Banks in Indonesia for the 2018-2022 period is more inclined towards Pecking Order Theory, where companies use internal funds more than external funds in the composition of the company's capital structure. It is hoped that this research can contribute to improving the performance of Sharia Commercial Banks in Indonesia through making appropriate and optimal capital structure decisions, as well as being a reference for investors in making investments and assessing the shares of Sharia Commercial Banks that are members of the Indonesia Stock Exchange (BEI).